Многокритериальный подход к оценке результативности научных проектов - Петровский, А. Б.; Ройзензон, Г. В.; Тихонов, И. П.; Балышев, А. В. (НТУ "ХПИ", 2009)
Существует достаточно большое число практических задач принятия решений, в которых требуется разработать интегральные показатели деятельности, например, оценка результативности фундаментальных исследований. В работе предложен новый подход к многокритериальной оценке результативности научных проектов и описаны результаты апробации подхода при экспертизе в Российском фонде фундаментальных исследований.

There is a large enough number of practical tasks of making decision, in which it is required to develop integral performance indicators, for example, estimation of effectiveness of fundamental researches. The new going is in-process offered near the multicriterion estimation of effectiveness of scientific projects and the results of approbation of approach are described at examination in the Russian fund of fundamental researches.
Multiple criteria approach to R&D project efficiency
Keywords: интегральные показатели деятельности; лицо принимающее решение; ЛПР; метод стратификации кортежей; integral performance indicators; multicriterion estimation